The Impeachment of Dilma Rousseff and the Political Instability in Latin America: the applicability of the Perez-Liñan’s model - Mendes, Gabriel Gutierrez (2018)
This article aims to analyze the recent impeachment episode of President Dilma Rousseff in Brazil, using the theoretical approach of the political scientist Anibal Perez-Liñan presented in his book "Presidential impeachment and the new political instability in Latin America". The main purpose is to verify the extent to which the features of the Perez-Liñan’s research model can be found in the Brazilian case. According to the author, in recent years, we have seen the establishment of a new pattern of political instability in the region of Latin America, where the chief executive is removed from the country's command through constitutional mechanisms. This paper tries to understand how the factors that constitutes the main axes of the author's approach, that is, mass manifestations, the dissemination of corruption scandals in the mass media, the tension between Legislative and Executive, contributed to the episode of Dilma’s impeachment.